2004
DOI: 10.1063/1.1764432
|View full text |Cite
|
Sign up to set email alerts
|

On nonlinear stability of the regular vortex systems on a sphere

Abstract: We present the necessary and sufficient conditions for stability and instability of the stationary rotation of a system of n identical point vortices located at the same latitude on a sphere at vertices of a regular n-gon. We also examine stability of the equilibrium configuration of identical point vortices, situated at the vertices of a regular polyhedra. It is proved that vortex tetrahedron, octahedron, and icosahedron are stable, while vortex cube and dodecahedron are unstable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…But the case of N = 7 (called the Thomson heptagon) was noticed as a peculiar configuration dividing stability and instability, which eventually turns out to be neutrally stable after several decades (see Boatto & Cabral (2003) for details). The ring of point vortices problem is generalized later and is investigated analogously for various underlying surfaces such as a sphere (Polvani & Dritschel 1993;Boatto & Cabral 2003;Boatto & Simo 2004;Kurakin 2004;Boatto & Simo 2008) or a cylinder (Souliere & Tokieda 2002;Montaldi et al 2003). In the same spirit, here we study the stability of a vortex ring on the spheroid as an application and also a concrete example of previous mathematical formulation.…”
Section: Latitudinal Ring Of Point Vortices On Ementioning
confidence: 99%
See 1 more Smart Citation
“…But the case of N = 7 (called the Thomson heptagon) was noticed as a peculiar configuration dividing stability and instability, which eventually turns out to be neutrally stable after several decades (see Boatto & Cabral (2003) for details). The ring of point vortices problem is generalized later and is investigated analogously for various underlying surfaces such as a sphere (Polvani & Dritschel 1993;Boatto & Cabral 2003;Boatto & Simo 2004;Kurakin 2004;Boatto & Simo 2008) or a cylinder (Souliere & Tokieda 2002;Montaldi et al 2003). In the same spirit, here we study the stability of a vortex ring on the spheroid as an application and also a concrete example of previous mathematical formulation.…”
Section: Latitudinal Ring Of Point Vortices On Ementioning
confidence: 99%
“…This problem originated from the classical work of Thomson (1883), in which the stability of point vortices on the edge of a regular n-gon is analysed in the plane. This study was subsequently generalized and has been applied to various underlying surfaces such as a cylinder (Souliere & Tokieda 2002;Montaldi et al 2003) and a sphere (Polvani & Dritschel 1993;Boatto & Cabral 2003;Boatto & Simo 2004;Kurakin 2004;Boatto & Simo 2008). The stability of the point vortex ring on a spheroid will be analysed by comparing it with the case of a sphere.…”
Section: Introductionmentioning
confidence: 99%
“…The expression (9) indicates that λ If ξ p η p < 0, then λ p is pure imaginary due to (9). Therefore we have the following stability proposition.…”
Section: Introductionmentioning
confidence: 94%
“…They showed that the range of the nonlinear stability coincided with that of the linear stability. Kurakin [9] recently considered the nonlinear stability in the sense of Routh and complemented the stability analysis of the N -ring on the sphere.…”
Section: Introductionmentioning
confidence: 99%
“…While the N -ring is one of the simplest models to approximate the evolution of such coherent structures, it is also one of relative equilibria of (1.1) and (1.2) discussed in [26]. Linear and nonlinear stability of the N -ring has been extensively investigated [3,5,20,37].…”
Section: Introductionmentioning
confidence: 99%